Household sector borrowing in the euro area - a micro data perspective - Ramón Adalid; Adriana Lojschová; Thomas Westermann (European Central Bank (ECB), 2011)
This paper uses micro data from the European Union Statistics on Income and Living Conditions (EU-SILC) to generate structural information for the euro area on the incidence of household indebtedness and the debt service burden. It breaks down incidence by characteristics such as income, age and employment status, all features that can be cross-referenced in the light of theories such as the life-cycle hypothesis. Overall, income appears to be the dominant feature determining the debt status of a household. The paper also examines the evolution of indebtedness and debt service burdens over time and compares the situation in the euro area with that in the United States. In general, the results suggest that the macroeconomic implications of indebtedness for monetary transmission and financial stability are not associated with the mean but with the tails of the distribution.
Keywords: C32; G14; 330; financial vulnerability; household indebtedness; Micro Survey Data; monetary transmission